An attractive alternative to prenatal diagnosis: a case report of preimplantation genetic testing in familial cardiomyopathy - Shubhra Pandey, MBBS, DGO, FRM; Parth Khandhedia, MBBS, DGO (AJOG Global Reports)
Familial hypertrophic cardiomyopathy is an autosomal dominant familial inherited heart disease caused by mutations in the sarcomere protein that affects nearly 1 in 500 people. Genetic testing is of immense importance for familial inherited diseases. This study aimed to determine a way to allow couples with either partner or both partners with familial disease to achieve a healthy biological child. Preimplantation genetic testing for monogenic disorders of the embryos is a new technique that identifies the causative mutation in the genome of family members. The embryo trophectoderm is biopsied at the blastocyst stage of development. Subsequently, embryos are made via in vitro fertilization, and 6 to 8 cells are biopsied from the trophectoderm of the day 5 blastocyst. A couple in their early 20s consulted the hospital for preconceptional counseling for a second child. Their first child was a girl who had a heterozygous variant of chr7:128844078C>T; (HET); c.3004C>T; p.Arg1002Trp on Exon 20 with a gene transcript of filamin C (+) ENST00000 325888.13. Preconceptional pretest genetic counseling of the couple regarding the genetic aspects of the severity of the mutation and its inheritance was conducted. A heterozygous missense variation was present in the asymptomatic father, whereas the mother was normal. Posttest genetic counseling was conducted using a multidisciplinary approach, and the parents were informed about the clinical implications and the possibility of risk of transmission. Preimplantation genetic testing for monogenic disorders was performed, and 6 of 10 embryos were abnormal. A frozen-thawed embryo transfer was performed that resulted in a singleton pregnancy and the term delivery of a healthy male child. Genetic testing of embryos assists clinicians in managing couples at risk of transmission of serious genetic disorders. For couples with familial disease in either partner, medically assisted reproduction with preimplantation genetic testing for monogenic disorders is a promising strategy to achieve a healthy biological child.